Essay on Human Aging from the Biophysical Perspective - Galindo Mosquera, Santiago Antonio (2018)
In this essay, a position is proposed regarding the definition of life from the biophysical point of view, which explains death as something inevitable in autonomous systems, but justifies the perpetuity of the species by the mechanism of reproduction. Incorrect approaches to human aging are criticized, because they refer more to the effects than to the causes, so this paper outlines a possible solution, based on an exogenous intervention strategy to violate the entropic principle. It is concluded that the total of the vital energy is equal to the energy expended minus the energy received, so that the aging and death of individuals would be the result of a bioenergetic imbalance.